ISOLATION, PHYLOGENETIC CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF STREPTOMYCES STRAINS ISOLATED FROM AIR AT WALAILAK UNIVERSITY - M. LERTCANAWANICHAKUL, (International Journal of Pharma and Bio Sciences, 2015)
Emergence of drug resistance among Staphylococcus aureus to currently used antibiotics has made the search for novel bioactive compounds from natural and unexplored habitats a necessity. In this study, isolation, characterization and antimicrobial activity of an actinomycete strain isolated from air at Scientific and Technological Equipments Building, Walailak University, located in Southern Thailand. Eight strains were done and identified as Streptomyces spp. using 16S rDNA sequence analysis. Streptomyces lydicus A2 exhibited antibacterial activity against Gram positive bacteria, Gram negative bacteria. Partial characterization of the active substance (resistance to heat) showed that it would be of non-protein nature. The production of the active substance showed that the production occurs between the 4th and 7th day of fermentation. This will open the way to further investigations to demonstrate their potential importance in combating pathogenic bacteria, methicillin resistant S. aureus.